In situ imaging, elemental and molecular spectroscopy for the analysis of the construction and painting of a Late Period coffin at the Egyptian Museum of Cairo. (March 2018) - Zidan, Eman H.; Mosca, Sara; Bellei, Sara; Frizzi, Tommaso; Gironda, Michele; El-Rifai, Ibrahim; Mahgoub, Hend; Sadik, Sabah; Gamal Rashed, Mohamed; Osticioli, Iacopo; Siano, Salvatore; Valentini, Gianluca; et al.
Graphical abstract: Highlights: A unique Late Period Coffin is studied at the Egyptian Museum Cairo. UV and IR imaging maps the presence of Egyptian Blue and other pigment mixtures. A lead ground is confirmed with Scanning Electron Microscopy and X-ray Fluorescence. Portable Raman spectroscopy has been used to map As-based pigments. Abstract: This works presents the analysis of polychrome objects using transportable instrumentation for the analysis and characterisation of the palette of Ancient Egyptian Objects from a Late-period coffin in the Egyptian Museum in Cairo, with a focus both on practical details of measurements and specific results from imaging and point-like analyses. Multispectral imaging was combined with X-ray fluorescence, Raman and Photoluminescence spectroscopies. All instrumentation was transported to the museum and analysis was carried out in situ within the Conservation Laboratory. Results demonstrate the strength of imaging for mapping the presence of Egyptian Blue and mixtures of the pigment, while elemental and molecular analyses indicate the presence of mixtures of pigments to create greens, and the selective use of yellow earth or yellow ochre. In situ analysis informed sampling to determine the type of wood used and the stratigraphy of the multiple layers of white pigments and cloth used to create the ground on which the painting was executed.